2010
DOI: 10.1002/tox.20492
|View full text |Cite
|
Sign up to set email alerts
|

Malathion‐induced oxidative stress, cytotoxicity, and genotoxicity in human liver carcinoma (HepG2) cells

Abstract: Malathion is an organophosphate pesticide that is known for its high toxicity to insects and low to moderate potency to humans and other mammals. Its toxicity has been associated with the inhibition of acetylcholinesterase activity, leading to the interference with the transmission of nerve impulse, accumulation of acetylcholine at synaptic junctions, and subsequent induction of adverse health effects including headache, dizziness, nausea, vomiting, bradycardia, and miosis. Oxidative stress (OS) has been repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
66
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(72 citation statements)
references
References 27 publications
6
66
0
Order By: Relevance
“…Cytotoxicity increased with concentration for both the pesticides, and malathion was more toxic when compared to monocrotophos. Similarly, concentration dependant increase in the toxicity of malathion was detected in grass carp cell line (Chen et al, 2006) and human liver carcinoma cell line (Moore et al, 2010). IC 50 of malathion ranged from 37.94 AE 1.93 mg l À1 for 12 h to 3.04 AE 0.27 mg l À1 for 72 h in grass carp cells (Chen et al, 2006).…”
mentioning
confidence: 71%
“…Cytotoxicity increased with concentration for both the pesticides, and malathion was more toxic when compared to monocrotophos. Similarly, concentration dependant increase in the toxicity of malathion was detected in grass carp cell line (Chen et al, 2006) and human liver carcinoma cell line (Moore et al, 2010). IC 50 of malathion ranged from 37.94 AE 1.93 mg l À1 for 12 h to 3.04 AE 0.27 mg l À1 for 72 h in grass carp cells (Chen et al, 2006).…”
mentioning
confidence: 71%
“…Studies conducted by Chandra and Khuda-Bukhsh (2004) and Klopman, Conttreras, Reosenkranz, and Waters, (1985) showed that during the metabolism of azadirachtin, electrophilic ions and free radicals are produced, which interact with the nucleophilic sites in DNA and lead to breaks and other related DNA damage. It is also reported that the oxidative stress in an organism plays an important role to inducing cytotoxicity and genotoxicity in different vital tissues (Moore, Yedjou, & Tchounwou, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…OPs are oxidants and impair enzymatic antioxidant defences, including superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPx), and glutathione S-transferase (GST) (23,34,44,(114)(115)(116)(117)(118)(119)(120)(121)(122)(123)(124)(125)(126)(127)(128)(129). Malathion, methyl parathion, and parathion in HepG2 cell lines, as well as chlorpyrifos, methidathion, chlorfenvinphos, and dimethoate in rat liver and diazinon in fish most probably disrupt membrane lipids through oxidative stress (23,35,61,116,118,(130)(131)(132)(133)(134)(135). Table 1 summarises the key changes in antioxidant defence and oxidative stress biomarkers caused by OPs.…”
Section: Possible Effects Of Ops On Hepatic Oxidative Stress Pathwaysmentioning
confidence: 99%
“…The mutagenic effects of OPs are owed to the direct alkylating ability of the parental molecule and its metabolites (130,131,155).…”
Section: Possible Mutagenic Genotoxic and Carcinogenic Effects Of Opsmentioning
confidence: 99%
See 1 more Smart Citation